Evolutionary economics and human nature - Laurent, John, 1947- (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2003)
This book addresses the question of human nature in economics, examining not only some of the recent writing on this subject in evolutionary psychology and related disciplines.
Includes bibliographical references and index.
osa 03/06/13
Keywords: Evolutionary economics; Psychology